2018
DOI: 10.21010/ajtcamv15i3.5
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Composition and Nutritive Analysis of Bulbine Abyssinica A. Rich. Used in the Treatment of Infections and Complications Associated With Diabetes Mellitus in the Eastern Cape Province, South Africa

Abstract: Background: B. abyssinica is a succulent member of the genus Bulbine (Asphodelaceae). It occurs from the Eastern Cape, through Swaziland and further north to Ethiopia. The species is used in traditional medicine to treat rheumatism, dysentery, bilharzia, cracked lips and diabetes. The tea leaf is used to treat cough, vaginal and bladder problems. Whereas B. abyssinica has ethno medicinal value, not much data concerning its phytonutrient, macro and micro element composition can be found in literature. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Thus, very interesting biological activities of these plants have been discovered, such as antimicrobial efficacy, against a diverse range of Gram-positive and Gram-negative bacteria (Van Vuuren, 2008 ; Nyila et al, 2012 ; Okem et al, 2012 ; Mabona et al, 2013 ; Sharma and Lall, 2014 ; Aro et al, 2015 ; Elisha et al, 2016 ; Kabongo-Kayoka et al, 2016 ; Ramadwa et al, 2017 ) in addition to a large spectrum of fungi (Adamu et al, 2012 ; Otang et al, 2012 ). Moreover, anticancer (Sharma and Lall, 2014 ; Saeed et al, 2016 ), antioxidant (Saeed et al, 2012 ; Sharma and Lall, 2014 ; Dzoyem and Eloff, 2015 ), anti-inflammatory (Dzoyem and Eloff, 2015 ), anthelmintic (Aremu et al, 2010 ; Maphosa et al, 2010 ; Maphosa and Masika, 2012 ; Okem et al, 2012 ), antimalarial (Clarkson et al, 2004 ), antiviral (Bagla et al, 2012 ; Mehrbod et al, 2018 ), antidiabetic (Oyedemi et al, 2009 ; Kibiti, 2016 ), anti-HIV (Kamng'ona et al, 2011 ; Hurinanthan, 2013 ; Mthethwa et al, 2014 ) activities have been reported. Comprehensive reviews and surveys have discussed the potential of South African plants to treat inflammatory conditions (Iwalewa et al, 2007 ), diarrhea (Lin et al, 2002 ; Mathabe et al, 2006 ; Fawole et al, 2009 ; Bisi-Johnson et al, 2010 ; Semenya and Maroyi, 2012 ; Van Vuuren et al, 2015 ; Motlhatlego et al, 2018 ) and TB-related symptoms (McGaw et al, 2008 ).…”
Section: What Makes South African Medicinal Plants a Unique Source Tomentioning
confidence: 99%
“…Thus, very interesting biological activities of these plants have been discovered, such as antimicrobial efficacy, against a diverse range of Gram-positive and Gram-negative bacteria (Van Vuuren, 2008 ; Nyila et al, 2012 ; Okem et al, 2012 ; Mabona et al, 2013 ; Sharma and Lall, 2014 ; Aro et al, 2015 ; Elisha et al, 2016 ; Kabongo-Kayoka et al, 2016 ; Ramadwa et al, 2017 ) in addition to a large spectrum of fungi (Adamu et al, 2012 ; Otang et al, 2012 ). Moreover, anticancer (Sharma and Lall, 2014 ; Saeed et al, 2016 ), antioxidant (Saeed et al, 2012 ; Sharma and Lall, 2014 ; Dzoyem and Eloff, 2015 ), anti-inflammatory (Dzoyem and Eloff, 2015 ), anthelmintic (Aremu et al, 2010 ; Maphosa et al, 2010 ; Maphosa and Masika, 2012 ; Okem et al, 2012 ), antimalarial (Clarkson et al, 2004 ), antiviral (Bagla et al, 2012 ; Mehrbod et al, 2018 ), antidiabetic (Oyedemi et al, 2009 ; Kibiti, 2016 ), anti-HIV (Kamng'ona et al, 2011 ; Hurinanthan, 2013 ; Mthethwa et al, 2014 ) activities have been reported. Comprehensive reviews and surveys have discussed the potential of South African plants to treat inflammatory conditions (Iwalewa et al, 2007 ), diarrhea (Lin et al, 2002 ; Mathabe et al, 2006 ; Fawole et al, 2009 ; Bisi-Johnson et al, 2010 ; Semenya and Maroyi, 2012 ; Van Vuuren et al, 2015 ; Motlhatlego et al, 2018 ) and TB-related symptoms (McGaw et al, 2008 ).…”
Section: What Makes South African Medicinal Plants a Unique Source Tomentioning
confidence: 99%